2022
DOI: 10.1111/obr.13419
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk of anemia and related micronutrient deficiencies after Roux‐en‐Y gastric bypass and sleeve gastrectomy in patients with obesity: An updated meta‐analysis of randomized controlled trials

Abstract: Summary Although Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy (SG) are the most prevalent bariatric surgical procedures, high‐level evidence is scarce regarding the assessment of postoperative nutritional risk in RYGB versus SG. Therefore, we performed a systematic review and meta‐analysis to compare the risk of anemia and related micronutrient deficiencies after RYGB and SG. We analyzed 10 randomized controlled trials that compared RYGB and SG with reported incidence of postoperative anemia and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Several retrospective studies 50,51 have shown a much lower incidence of anemia and related nutrient deficiencies following SG than following RYGB, suggesting that a looser nutritional monitoring regimen might be undertaken after SG. However, a recent meta‐analysis by Kwon et al 52 that combined 10 RCTs discovered that the risk of postoperative anemia and iron and folate deficiencies following SG was comparable to that of RYGB. The inconsistent outcomes among studies are primarily attributable to small sample sizes, unspecified time points for follow‐up, and differences in nutritional supplementation strategies, which complicate therapeutic practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several retrospective studies 50,51 have shown a much lower incidence of anemia and related nutrient deficiencies following SG than following RYGB, suggesting that a looser nutritional monitoring regimen might be undertaken after SG. However, a recent meta‐analysis by Kwon et al 52 that combined 10 RCTs discovered that the risk of postoperative anemia and iron and folate deficiencies following SG was comparable to that of RYGB. The inconsistent outcomes among studies are primarily attributable to small sample sizes, unspecified time points for follow‐up, and differences in nutritional supplementation strategies, which complicate therapeutic practice.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 illustrates the overall estimates of the prevalence of nutrient deficiencies after SG. The pooled prevalence of patients with ferritin deficiency was 6% (95% CI [4,9], I 2 = 92%) at baseline, rising to 12% (95% CI [8,16], I 2 = 93%) at 12 months after surgery, and increasing steadily to 15% (95% CI [8,23], I 2 = 94%) at 24 months, 18% (95% CI [5,35], I 2 = 97%) at 36 months, 22% (95% CI [9,39], I 2 = 95%) at 48 months, and 27% (95% CI [9,52], I 2 = 90%) at 60 months. The pooled prevalence of iron deficiency decreased from 13% (95% CI [7,20], I 2 = 97%) at baseline, to 6% (95% CI [1,14], I 2 = 93%) at 24 months, and then increased to 12% (95% CI [5,23], I 2 = 93%) at 36 months, 16% (95% CI [5,32], I 2 = 95%) at 48 months, and 20% (95% CI [7,37], I 2 = 85%) at 60 months.…”
Section: Prevalence Of Nutrient Deficienciesmentioning
confidence: 98%
See 1 more Smart Citation
“…Biliopancreatic diversion, the most effective operation for weight reduction, produces the greatest degree of malabsorption [ 30 ]. In addition, malabsorption of micronutrients such as iron often necessitate lifelong supplementation [ 31 , 32 ]. However, at least for RYGB and VSG, the effects on macronutrient malabsorption are generally small and cannot fully explain the large and sustained weight loss.…”
Section: Bariatric Surgery Changes Gut-brain Communicationmentioning
confidence: 99%
“…While SG is primarily considered a restrictive procedure, the reduction in gastric acid production and intrinsic factor secretion due to removal of a large part of the stomach may also affect absorption of micronutrients [2]. Contrary to initial belief, similar rates of long-term nutritional deficiencies are found in SG patients when compared to patients that have undergone Roux-en-Y gastric bypass, even though the intestinal surface area remains intact following SG [3][4][5][6]. Micronutrient deficiencies for vitamin D, vitamin B12, and iron as well as elevated parathyroid hormone (PTH) levels have been reported up to 5 years after SG [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%